Review on Enhanced WDM-OFDM-PON System Using Modulation Technique - Dangi, Pooja; Shrivastava, Manish (International Journal of Computer Sciences and Engineering, 2019)
Studies among the field communication system existing technique and proposes and by experimentation demonstrate a multiuser wavelength-division-multiplexing passive optical network (WDM-PON) system combining with orthogonal frequency division multiple (OFDM) technique. A tunable multiwavelength optical comb is intended to provide flat optical lines for helping the configuration of the multiple source-free optical network units WDM-OFDM-PON system supported normal single mode fiber (SSMF). In WDM based on fiber optical network communications using wavelength with multiplex or demultiplex may be a technology that multiplexes variety of optical carrier signals onto one fiber by victimization completely different wavelengths of optical device lightweight. this system allows bidirectional communications over one strand of fiber, also as multiplication of capability and calculate BER (Bit Error Rate) and OSNR (optical signal noise ratio) finally; a comparison of by experimentation achieved receiver sensitivities and transmission distances victimization these receivers is given. The very best spectral potency and longest transmission distance at the very best bit rate. WDM based many applications like transmission data, medical imaging data, and digital audio data and video conferencing data are information measure-intensive with the Advance in optical technology providing verdant bandwidth, it`s natural to increase the multicast construct to optical networks so as to realize increased performance. Our projected scheme (PGA) based on information load transmitted capability improve supported higher information transmitted over these channels and high data up to develop in Matlab tool and using optical interleaver the OFDM model and analysis the performance of WDM-PON system.